NUTRITION ALMANAC - Kirschmann, Gayla J.; Kirschmann, John D. (McGraw-Hill, 1996)
The three previous editions of this broadly popular reference have brought simple, sensible, and accurate nutrition information to an eager audience of health-conscious readers. This edition continues the high standards set by its forebears, offering sound, down-to-earth advice on health and nutrition in an easygoing style. As before, this book aims to empower readers to take charge of their own health. Illnesses can be prevented, say the authors, through knowledge and use of proper nutrition. They call on an increasing body of scientific evidence to back their arguments that vitamin and mineral supplements can also be effective tools in disease prevention and cure. Remedies such as herbal medicine and alternative treatments including homeopathy are also explored. Tables and charts give accurate nutrition data on most common foods